Differences in mechanisms underlying reinstatement of cigarette smoke extract- and nicotine-seeking behavior in rats. (1st January 2020) - Cross, Sarah J.; Reynaga, Daisy D.; Cano, Michelle; Belluzzi, James D.; Zaveri, Nurulain T.; Leslie, Frances M.
Abstract: Despite extensive research, current therapies for smoking cessation are largely ineffective at maintaining abstinence for more than a year. Whereas most preclinical studies use nicotine alone, the goal of the present study was to evaluate whether inclusion of non-nicotine tobacco constituents provides better face validity for the development of new pharmacological therapies for smoking cessation. Here, we trained adult male rats to self-administer nicotine alone or cigarette smoke extract (CSE), which contains nicotine and other aqueous constituents of cigarette smoke. After stable self-administration behavior was established, animals underwent extinction training followed by drug and cue primed reinstatement testing. We show that animals that self-administered CSE had significant reinstatement in all drug and drug + cue stimulus conditions whereas animals that self-administered nicotine only showed significant reinstatement in the drug + cue conditions. AT-1001, an α3β4 nicotinic acetylcholine receptor (nAChR) functional antagonist, attenuated drug + cue-primed reinstatement of both CSE- and nicotine-seeking behavior. However, AT-1001 was less potent in blocking drug-primed reinstatement in animals that had self-administered CSE than in those that had self-administered nicotine alone. This was the case even when nicotine was used to prime reinstatement in animals that had self-administered CSE, suggesting that prior CSE exposure had altered the functional role of α3β4-containing nAChRs in drug-seeking behavior. These findings confirm the importance of non-nicotine tobacco constituents and α3β4* nAChRs in cue- and nicotine-primed craving. They also suggest that tests using CSE may be more valid models to study tobacco dependence than use of nicotine alone. Highlights: α3β4* nAChRs are a potential pharmacological target for smoking cessation. Aqueous tobacco smoke constituents (i.e., CSE) potentiate nicotine reinstatement. The α3β4 functional antagonist AT-1001 reduces nicotine-seeking behavior. AT-1001 is less potent at inhibiting CSE reinstatement than nicotine reinstatement.